Emergent Plutonomy in India: Limits of Transformative Constitutionalism - Dar, Rouf Ahmad; Dar, Javid Ahmad; Wani, Aejaz Ahmad (Economic and Political Weekly, 2025)
The problem of plutonomy in contemporary India is spelled out. The inclusion of economic rights, justice, and equality in national constitutions is surveyed to evaluate their effectiveness in preventing wealth inequality. The debates in the Constituent Assembly of India are studied to foreground the fears that interspersed around economic inequality. In doing so, questions are raised on the transformative aspects of the Constitution of India, arguing that - despite possessing the potential to check the concentration of wealth and ensure economic equality - it has implicitly and explicitly allowed plutonomy issues.
Keywords: Constitutionalism; Economic Rights; Liberal Democracies; Plutonomy; Global Economy